GLOBAL EPIDEMIOLOGY OF VIRAL HEPATITIS: CURRENT STATUS AND FUTURE FORECAST (The Conference Hub, 2025)
Viral hepatitis is one of the most widespread and serious public health concerns worldwide. Hepatitis A, B, C, D, and E viruses infect humans through various routes and can cause both acute and chronic diseases. According to the World Health Organization (WHO), millions of people worldwide contract hepatitis infections annually, leading to severe complications such as liver cirrhosis and liver cancer. On a global scale, hepatitis B and C are the most dangerous types, as they often progress to chronic conditions, causing severe health consequences.